Perancang Aplikasi Game Cangkulan (Kartu Remi) Denganmenerapkan Kombinasi Algoritme Fisher Yatesshuffle Danlinear Congruent Method - Hari Setiawan Asri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Games are a type of entertainment that is liked by everyone from the age of children, adults and the elderly. Besides being used to relieve fatigue in activities, a game can also function to train a person's mindset to find solutions to solve a problem that exists in a game. In the past, games were played traditionally such as card games, chess, snakes and ladders, hide and seek, and others. Along with the development of technology, the game was developed into more modern technology, such as computers (PCs) or smartphones. Playing cards or hoe is a game with big cards that play two or four people, a player lowers from the same group of pictures, the winner is considered finished if one of them spends his cards. Randomization in hoop games is very important, because randomization is what makes the game interesting to complete. This could be avoided if the Fisher Yates shuffle (named after its inventors Ronald Fisher and Frank Yates) was used to change the order of randomly assigned entries. The permutations generated by this algorithm appear with the same probability. This algorithm is declared biased because the permutations generated by this algorithm appear with the same probability. This is evidenced by the experiment of randomizing a set of cards that is repeated